ACC Limited : Project 30-30 - Mukherjee, Saral; Raghuram, G., 1955-; Chetan Soman (London : Indian Institute of Management, Ahmedabad, 2011)
ACC limited had set itself a challenging target of producing and selling 30 million tonnes of concrete in 2011. The problem however, was that those 30 million tonnes of concrete needed to be transported putting a huge strain on logistics. The focus of the case is on analysing the supply chain in an integrated manner, considering the options of ACC to increase their market presence.
Originally published in Mukherjee, S., Raghuram, G., & Soman, C. (2011). ACC Limited: Project 30-30. PROD0295. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ACC Limited; Business logistics; Success in business